A Computational Bibliometric Analysis of Game Advertising using VOSviewer - Ginting, Yogie Rinaldy (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
The purpose of this study is to perform a computational bibliometric analysis of the Term “Game advertising” by combining mapping analysis using VOSviewer Publish or Perish software, and Google Schoolar. The method used is a bibliometric and descriptive quantitative approach. The data obtained is a search result based on the keyword "Game Advertising" on Google Scholar. The search results show 989 articles published from 2017 to 2022 decreasing every year except in 2021. This can be proven in 2017 with 232 articles, in 2018 it decreased to 210 articles, in 2019 it decreased again to 199 articles. In 2020 it decreased to 136 articles, except for in 2021 there was a less significant increase to 137 articles, and in 2022 research on Game Advertising decreased dramatically, the number of publications to 40. The conclusion of this study shows the importance of conducting bibliometric analysis, especially in advertising games field. This research is expected to be a reference for further research in determining and analyzing the research theme.